Tauhid View Tuan Guru Umar Kelayu: Intellectual History Study of Lombok Theologian Central Figure - Tohri, Ahmad; Rasyad, Abdul; Habibuddin, Habibuddin; Zulkarnain, Zulkarnain (Paramita: Historical Studies Journal, 2022)
Tuan Guru Umar Kelayu (TGU) was one of the pioneers and a central figure born in the era of the teacher-teaching of the Sasak-Lombok community. The purpose of this study is to analyze the monotheistic view of TGU as the central figure of Lombok clerics in the study of intellectual history. The research method used is the historical method, which is a process of critically analyzing records and experiences or relics of the past. The results showed that TGU as a teacher early generation was born from a family that has a breed very strong with the Islamic Selaparang Kingdom by mastering religious knowledge broadly and deeply which was obtained from scholars in Lombok, the archipelago, and the world. The wisdom of TGU is reflected in the book of monotheism written at the age of ± 25 years, with the title Manzarul Amrad. The systematic thinking, perspective, and narrative style are unique in writing the book of monotheism that distinguishes it from other scholars. The monotheistic view of TGU has an impact on strengthening Islam, especially strengthening the faith of the Sasak-Islamic community. Instilling the spirit of jihad fi sabilillah, the Sasak people fought against the Balinese and Dutch rulers. TGU is involved in the dialectic of Islamic intellectuals through a network of teachers, friends, and students in Lombok, the archipelago, and even the Islamic world.Tuan Guru Umar Kelayu (TGU) merupakan salah seorang perintis dan tokoh sentral kelahiran era ke-tuan guru-an masyarakat Sasak-Lombok. Tujuan penelitian menganalisis pandangan tauhid TGU sebagai tokoh sentral ulama Lombok dalam kajian sejarah intelektual. Metode penelitian yang digunakan metode sejarah, yaitu suatu proses menganalisis secara kritis rekaman dan pengalaman atau peninggalan masa lampau. Hasil penelitian menunjukkan TGU sebagai tuan guru generasi awal terlahir dari keluarga yang memiliki trah sangat kuat dengan Kerajaan Selaparang Islam dengan menguasai ilmu agama secara luas dan mendalam yang diperoleh dari para ulama di Lombok, Nusantara, dan dunia. Kealiman TGU tercermin dari kitab tauhid ditulis pada usia ±25 tahun, dengan judul Manzarul Amrad. Sistematika berpikir, cara pandang, dan gaya narasi merupakan keunikan dalam menulis kitab tauhid yang membedakannya dengan ulama-ulama lain. Pandangan tauhid TGU berdampak terhadap penguatan keislaman terutama peneguhan akidah masyarakat Islam-Sasak. Menanamkan semangat jihad fi sabilillah rakyat Sasak melakukan perlawanan pada penguasa Bali dan Belanda. TGU terlibat dalam dialektika intelektual keislaman melalui jaringan guru, sahabat, dan murid di Lombok, Nusantara, bahkan dunia Islam.Cite this article: Tohri, A., Rasyad, A. Habibuddin, Zulkarnain (2022). Tauhid View Tuan Guru Umar Kelayu: Intellectual History Study of Lombok Theologian Central Figure. Paramita: Historical Studies Journal, 32(1), 1-10. http://dx.doi.org/10.15294/paramita.v32i1.26636